Enhanced education for adult patients with persistent post-concussion headaches: a randomized controlled trial - Emily Collett; Tianru Wang; Candice Todd; Anil Dosaj; Andrew Baker; Cindy Hunt (Concussion)
Aim & Patients: We conducted a randomized clinical trial to determine if an e-learning intervention can enhance recovery in adult patients with persistent post-concussion headaches (PPCH). Materials & Methods: The intervention consisted of three e-learning modules administered at baseline, 6 and 12 weeks. Data were collected on symptoms, community integration, quality of life and healthcare utilization at baseline and 12-week follow-up. ANCOVA was conducted to compare changes. Results: No statistically significant difference was observed on symptoms although we observed a trend toward reduced healthcare utilization and improved quality of life in the intervention group. Conclusion: E-learning modules for patients experiencing PPCH warrant further investigation with data on participant compliance and measures focusing on simpler short-term outcomes. Clinical Trial Registration: NCT03391583 (ClinicalTrials.gov)